Radial extracorporeal shock wave therapy for the management of spasticity in cerebral palsy: study protocol for a randomized controlled trial - Tur Segura, Míriam; Gimeno Esteve, Francisca; Biedermann Villagra, Tamara; Jiménez Redondo, Jordi; García Rodríguez, Nicolás; Milà Villarroel, Raimon (Frontiers in Neurology, 2024)
Background: Spasticity is the most common motor disorder in cerebral palsy (CP), and its management is complex, posing a significant challenge for the rehabilitation team. Radial Extracorporeal Shockwave Therapy (rESWT) has emerged in recent years as an effective, noninvasive, and low-risk alternative for the management of spasticity in CP patients, with only minor side effects such as small bruises or discomfort during application. There is great variability in rESWT administration protocols, ranging from a single session up to the 12 sessions. The most extensively studied protocol involves 3 rESWT sessions with a one-week interval between session. According to current literature, the effect of rESWT has not been investigated by extending the time interval between sessions beyond one week to determine if therapeutic effects on spasticity can be prolonged over time.Methods: Following a power calculation using the minimal clinical important difference of our primary outcome (R2 of Modified Tardieu Scale), 72 patients will be included in the study. Enrolment is based upon inclusion/exclusion criteria outlined in the Methods section. Participants will be randomized in 3 groups. Each patient will receive 2000 impulses in the Triceps Sural muscle (distributed by all the plantar flexor muscles: soleus and gastrocnemius), at a 2.2 Bars pressure and a frequency of 8Hz. The Control Group will receive 3 rESWT sessions with a time interval of 1 week between each session. The Experimental Group A will receive 3 rESTW sessions with a time interval of 2 weeks between each session and the Experimental Group B will receive 3 rESTW sessions with a time interval of 4 weeks between each session.Discussion: This study will provide further information regarding the effect of rESWT on spasticity in patients with CP. If an increase in the time interval between rESWT sessions allows for the prolongation of therapeutic benefits on spasticity, it will be clinically relevant fact. With the same treatment dosage, patients will be able to benefit from its effects for a longer period of time.